Multidermatomal herpes zoster in an immunocompetent, fully vaccinated 17-year-old female: a case report - Katherine Teixeira; Shannon Williams; Spencer Morton; Amanda Harding (Journal of Medical Case Reports)
Abstract Background Herpes zoster, commonly known as shingles, results from the reactivation of varicella zoster virus, typically occurring in older adults. The advent of varicella vaccination has caused a decline in primary varicella infection cases; however, herpes zoster still occurs, albeit rarely, in fully vaccinated children. Case presentation This report presents a case of herpes zoster in a fully vaccinated 17-year-old white American female, highlighting the importance of considering herpes zoster in immunocompetent, vaccinated children. The patient presented with a rash along multiple dermatomes, which spread despite antiviral treatment. After completion of the antiviral treatment, the rash eventually receded, and she was left with no residual symptoms. Conclusion This case underscores the need for clinicians to recognize and manage uncommon diseases such as herpes zoster in the pediatric population, regardless of vaccination status, to prevent adverse outcomes. Although this patient did not have any residual symptoms, mortality, or morbidity, there could be a high probability for complications if there becomes optical or meningeal involvement.